Help-seeking intentions for early dementia diagnosis in a sample of Irish adults - Devoy, Susan; Simpson, Ellen Elizabeth Anne (Aging & mental health, 2017)
Objectives: To identify factors that may increase intentions to seek help for an early dementia diagnosis. Early dementia diagnosis in Ireland is low, reducing the opportunity for intervention, which can delay progression, reduce psychological distress and increase social supports. Method: Using the theory of planned behaviour (TPB), and a mixed methods approach, three focus groups were conducted (N = 22) to illicit attitudes and beliefs about help seeking for an early dementia diagnosis. The findings informed the development of the Help Seeking Intentions for Early Dementia Diagnosis (HSIEDD) questionnaire which was piloted and then administered to a sample of community dwelling adults from Dublin and Kildare (N = 95). Results: Content analysis revealed participants held knowledge of the symptoms of dementia but not about available interventions. Facilitators of help seeking were family, friends and peers alongside well informed health professionals. Barriers to seeking help were a lack of knowledge, fear, loss, stigma and inaccessible services. The quantitative findings suggest the TPB constructs account for almost 28% of the variance in intentions to seek help for an early diagnosis of dementia, after controlling for sociodemographic variables and knowledge of dementia. In the final step of the regression analysis, the main predictors of help seeking were knowledge of dementia and subjective norm, accounting for 6% and 8% of the variance, respectively. Conclusion: Future interventions should aim to increase awareness of the support available to those experiencing early memory problems, and should highlight the supportive role that family, friends, peers and health professionals could provide.